THE STUDENTS’ POINT OF VIEW TOWARD THE USE OF KAHOOT! AS THE TOOLS OF LEARNING ENGLISH - Octa Pratama Putra; Muchlas Suseno; Samsi Setiadi (IKIP Siliwangi, 2022)
The aim of this study is headed to decide students' perceptions by using Kahoot! in learning English and it is about to seek for the problems of the use of it. This study uses a qualitative research approach. The subjects of this study; there are 10 students of the Academy of English; English Major Institute. Data are collected by using the open-ended interview. The data analysis within this study uses a qualitative descriptive. For analysing the data, this study refers to be coding analysis consisting of data reduction, data presentation, and the drawn conclusion. This research reveals that, the benefits of using Kahoot! as follow: (1) having a positive competition, (2) helping students to be focusing more, (3) constructing a good situation in the classroom (4) encouraging & motivating students to keep learning more. Then, several of problems which is the issue of using Kahoot! they are (1) the internet connection is not stable, and (2) having more time for teaching by using it beforehand. Keywords: Kahoot, Games-based Learning Application, Students’ Point of View